The effect of higher-achieving peers on major choices and labor market outcomes - Jan Feld; Ulf Zölitz (University of Zurich, Department of Economics, 2021)
This paper investigates how exposure to higher-achieving male and female peers in university affects students' major choices and labor market outcomes. For identification of causal effects, we exploit the random assignment of students to university sections in first-year compulsory courses. We present two main results. First, studying with higher-achieving peers has no statistically significant or economically meaningful effects on educational choices. Second, we find suggestive evidence that women who have been exposed to higher achieving male peers end up in jobs in which they are more satisfied.
Keywords: I21; I24; J24; 330; Gender; major choice; peer effects